UMA SEQUÊNCIA DIDÁTICA PARA O ENSINO DA UNIDADE TEMÁTICA VIDA E EVOLUÇÃO PARA ALUNOS DO 7O ANO DO ENSINO FUNDAMENTAL: PROPOSTA A PARTIR DA UTILIZAÇÃO DA KHAN ACADEMY - Silveira, Edson Romário Duarte da (2024)
This research, linked to the Professional Master's Program in Science and Mathematics Teaching at Franciscana University, aimed to investigate the contributions that a didactic sequence, built from the Khan Academy platform, brings to the teaching of the thematic unit "Life and Evolution" for seventh grade students in Elementary School. The Khan Academy platform is a learning resource that can be used both in distance learning and as support for face-to-face teaching. The actions of this study were developed in a municipal school in Santa Maria/RS, with a seventh grade class, composed of 14 students with a heterogeneous profile and ages between 13 and 15 years old. Data collection was carried out through audio recordings and photos, which allowed for a complete record of classroom interactions. In addition, students' responses to different activities developed in the didactic sequence were collected. For data analysis, the principles of descriptive and explanatory research were used. The results of this study indicated that students were able to successfully complete most of the tasks proposed over the eight lessons that used the Khan Academy as a teaching resource. It is noticeable that students demonstrated engagement and interest in the classes, taking advantage of the interactive and personalized approach offered by the platform, as well as other activities. Throughout the didactic sequence, topics such as pollution and scarcity of natural resources were addressed, increasing students' understanding of how human actions affect nature. The field day, with a visit to Arroio Cadena, provided an enriching experience, allowing students to see firsthand the situation of nature in that space and the effects of human action on the stream banks. The experimentation class also allowed students to apply the acquired knowledge in a practical way and develop their scientific skills.